Elements of democracy - Obsanjo, Olusegun; Mabogunje, Akin L. (Abeokuta, Nigeria : ALF Publications, 1992)
The book is divided into four sections. The first section forms the basis of democracy; the second focuses on the institution and processes in democracy; the third dwells on the fruits of democracy; while the last section focuses on the necessary ingredients for the sustenance of the democracy.
Includes bibliographical references and index.
aia 22/11/2017
Loans
Keywords: Democracy; Political rights; Political participation; Nigeria